TOBACCO TAX INITIATIVE, TOBACCO COMPANY STATEMENT (Tufts Archival Research Center, 2007)
Californians Against Unfair Tax Increases (CAUTI) tobacco tax initiative tobacco company statement. Discusses creation of the Coalition for a Healthy California. Gives contact number for CAUTI. Urges readers to take a closer look at the proposition and its "deceptive provisions." Accuses proposition of being unfair, selfish, and not motivated by health reasons.